El Gaucho y el Comerciante. Dos modelos político-económico-sociales de los primeros tiempos de la independencia latinoamericana - Chalupa, Jirí (Diálogos Latinoamericanos, 2012)
The article analyzes the bases and results of Rosas´ regime in Argentina and Portales’ political system in Chile. The author compares and evaluates the Chilean and Argentinian solution to the chaotic situation that occurred after the expulsion of the Spaniards from Latin America. It seems that the two apparently very different regimes of Argentine dictator Juan Manuel de Rosas and the Chilean statesman Diego Portales hide a surprising number of similar or even identical elements.